Burning mouth syndrome: a literary review and an uptade - Matteo Mazzuka; Gianluca Botticelli; Enrico Ivagnes; Antonino Spagnolo; Sara Caruso; Roberto Gatto (Publymed, 2021)
Burning mouth syndrome is a debilitating condition of chronic oral pain and/or burning, which mainly affects pre and postmenopausal women. It can be characterized by the presence of other symptoms, such as a sensation of dry mouth (xerostomia), a bitter or metallic taste (dysgeusia) and tingling. BMS can be classified into two clinical forms: primary and secondary BMS. The primary BMS is essential or idiopathic, in which the organic local/systemic causes cannot be identified.